Balap Karung Sebagai Strategi Latihan Berbasis Permainan untuk Meningkatkan Daya Ledak dan Keseimbangan Atlet Senam Usia Dini - Muhammad Fitrah Mubarak; Swandika Pinem; Abdul Bashir Nur Hasani; Fachrun Nisa Sofiyah Khasanah; Indra Yudistira; Astini Asri; Toni Kogoya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The objective of this study was to examine the effectiveness of sack race training as a game-based training strategy in improving explosive power and balance in early-age gymnasts (aged 6-9 years) compared to conventional training methods. A quantitative approach was employed using a quasi-experimental design, specifically a pretest-posttest control group design. The sample consisted of 30 gymnasts who were divided into two groups: an experimental group (sack race training) and a control group (conventional training). The intervention was conducted twice a week for 12 sessions. The instruments used were the Vertical Jump test to measure explosive power and the Stork Stand Test to measure balance. Data were analyzed using the Mann-Whitney test for explosive power and the Independent t-test for balance at a significance level of 0.05. The results showed that (1) the experimental group experienced an increase in explosive power of 16.20 (p=0.004); (2) an increase in balance of 20.58 (p=0.026); (3) the control group only increased by 8.24 in explosive power; and (4) 8.62 in balance. The conclusion of this study is that sack race training has a significant effect on improving explosive power and balance in early-age gymnasts and is more effective than conventional methods. The sack race is recommended as a fun, measurable alternative training method for children's gymnastics coaches. Keywords: Sack Race, Explosive Power, Balance, Early-Age Gymnasts